Medical Education Metaverses (MedEd Metaverses): Opportunities, Use Case, and Guidelines - Yosra Magdi Mekki (21673721) (2025)
This article explores how artificial intelligence (AI), particularly generative AI (GenAI), can enhance extended reality (XR) applications in medical education (MedEd) metaverses. We compare traditional augmented reality/virtual reality methods with AI-enabled XR metaverses, highlighting improvements in immersive learning, adaptive feedback, personalized performance tracking, remote training, and resource efficiency. Other Information Published in: Computer License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1109/mc.2024.3474033